Stent-assisted coil embolization of a recurrent posterior cerebral artery aneurysm following surgical clipping - Takeshita, Tomonori (Neuroradiol J, 2016)
Posterior cerebral artery (PCA) aneurysms are rare, and direct surgery of these is considered difficult. Coil embolization of PCA aneurysms is becoming popular. However, it is difficult to completely obliterate the aneurysm while preserving the flow of the parent artery in large or giant PCA aneurysms with a wide neck with this technique. We report a case of a large and wide-necked PCA aneurysm with multiple recurrences following successful surgical clipping and coil embolization. A 77-year-old man with a large unruptured right PCA (P2) aneurysm was successfully treated by surgical clipping. Postoperative digital subtraction angiography (DSA) showed complete aneurismal occlusion. Four years afterward, the aneurysm recurred and grew toward the contralateral. Surgical retreatment of this complicated aneurysm was considered difficult, with a substantial risk of complications. Therefore, the aneurysm was treated with an endovascular procedure. Because simple coil embolization was not expected to achieve satisfactory obliteration of the aneurysm with preservation of parent artery patency, we used stent-assisted coil embolization. The patient tolerated the treatment well. On DSA obtained six months after the first endovascular treatment, coil compaction and recanalization of the aneurysm were detected. A second coil embolization was successfully performed without any complications. The aneurysm was stable during the next six-month follow-up. Stent-assisted coil embolization may be feasible and effective for such postoperatively complicated aneurysms.